The formulation of agar-based sustained release tablet of chlorpheniramine - Muharam, Muhammad Aiman (2016)
The objective of this study was to formulate a sustained released tablet of chlorpheniramine by using different concentration of agar. Sustained released tablets were prepared using agar as polymer, lactose as filler and chlorpheniramine as active ingredient. The tablets were analyzed in terms of swelling index and dissolution profile. Results from the study showed that formulation with 10% agar followed zero ordered drug release profile and has highest percentage of swelling. This proved that agar-based sustained release chlorpheniramine tablet has advantage over normal release tablets.